METODE PENDIDIKAN RELASI GENDER DALAM KELUARGA NABI MUHAMMAD SAW - Nur Arfiyah Febriani; Moh Aman; Armai Arief (Raudhah - Proud To Be Professional, 2023)
Inequality in gender relations in the family due to a lack of understanding of gender relations and wrong habits does not only give rise to cases of domestic violence (domestic violence). However, this inequality in relations has also given rise to the problem of a fatherless country, namely the lack of involvement of a father in educating children in the family, which has become a very serious threat. Therefore, this research aims to find patterns of gender relations in the family of the Prophet Muhammad SAW to become an example for human life in fostering gender relations in the family. The method used in this research is a qualitative method using library data sources through a descriptive analysis process. The results of this research found that there is a concept of gender relations education methods in the family of the Prophet Muhammad SAW which includes various methods, namely methods of service, independence, responsibility, deliberation, dialogue and listening.